Meningkatkan Prestasi Belajar PKN melalui Model Think-Pair-Share di SD Negeri Sungkai - Din Hadi, Mohamad; Ilyas Iskandar, Moh.; Muhamad, Muhamad (Attractive : Innovative Education Journal, 2022)
Based on the conditions in the class students are less active and think critically in the teaching and learning process. students face new contextual problems that are different from those exemplified, students have not been able to think critically and find solutions correctly. This research is based on the following problems: (a) increasing Civics learning achievement by applying the Think Pair Share cooperative learning method? (b) the effect of the Learning Method on the motivation to learn Civics?. This study uses three cycles of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is the fourth grade students of SDN Sungkai State for the academic year 2020/2021. The data obtained in the form of formative test results, observation sheets of student learning activities. From the results of the analysis obtained that student learning achievement has increased from pre-cycles that do not pass 50% pass 50%, cycle I who do not pass 30% pass 70%, cycle II does not pass 20% pass 80% and cycle III does not pass 10 % pass 90%. The conclusion of this study is that the learning method with the Think Pair Share model can have a positive effect on the achievement and learning outcomes of Class IV SDN Sungkai State Elementary School students in the 2020/2021 academic year, and this learning model can be used as an alternative model for Civics learning Keywords: Improving Learning Achievement, Think-Pair-Share, Learning Achievement